SKENARIO REGENERASI SEBAGAI INTERVENSI AKUPUNKTUR PERKOTAAN DI KAWASAN JALAN JAKSA, JAKARTA - Kevin Adrian; Maria Veronica Gandha (Jurusan Arsitektur dan Perencanaan, 2023)
The development of the city tends to have a negative impact on Jaksa Street tourist area which results in its degradation. Degradation on the once famous street among backpackers is marked by the closures of cafes and restaurants, as well as the increased number of properties that are up for rent or sale. The degrading trend that the street faces leads to changes in the sense of place, which may lead to a change in the character of Jaksa Street, which in the long run could include the death of the once famous tourist corridor. In an effort to maintain the sustainability of the area and the area’s character which holds collective memories for both the local community and tourists, an intervention needs to be carried out to ensure Jaksa Street continuity and survival. This study aims to develop a street development scenario and development plans for abandoned spaces along the street which are designed to partake in solving Jaksa Street problems. Analysis is carried out by using qualitative methods with primary data obtained by interviews and field visits as well as secondary data obtained from other sources. Urban acupuncture approach is used as a base for the development scenario of the area. The ultimate goal of this study is to develop a street development scenario and intervention plans that can answer existing problems and maintain the sustainability of Jaksa Street. Keywords: area character; attraction; degradation; tourist area Abstrak Perkembangan kota cenderung berdampak negatif terhadap kawasan wisata Jalan Jaksa yang mengakibatkan terjadinya degradasi. Degradasi pada kawasan yang terkenal di kalangan turis ransel ini ditandai dengan tutupnya kafe dan restoran serta jual beli bangunan. Tren degradasi Jalan Jaksa mendorong terjadinya perubahan pengalaman ruang, yang dapat menyebabkan perubahan karakter dan termasuk matinya kawasan wisata Jalan Jaksa di masa depan. Dalam upaya menjaga keberlangsungan kawasan dan karakter kawasan yang menyimpan kenangan kolektif baik bagi masyarakat lokal maupun turis mancanegara, sebuah intervensi perlu dilakukan untuk menjamin keberlangsungan kawasan wisata Jalan Jaksa. Tulisan ini bertujuan untuk membentuk sebuah skenario pengembangan kawasan serta rencana pengembangan untuk ruang-ruang yang ditinggalkan sehingga dapat berperan dalam penyelesaian masalah koridor Jalan Jaksa. Analisis menggunakan metode kualitatif dengan data primer yang diperoleh dengan wawancara dan kunjungan lapangan serta data sekunder yang diperoleh dari sumber lain. Dasar perancangan kawasan dilakukan dengan pendekatan akupunktur perkotaan. Tujuan akhir dari tulisan ini adalah untuk menunjukkan skenario pengembangan kawasan dan rencana pengembangan titik-titik intervensi yang dapat menjawab permasalahan yang ada dan menjaga keberlanjutan kawasan wisata Jalan Jaksa.